ANALISIS RISIKO MESIN BUBUT DI POLITEKNIK PERKAPALAN NEGERI SURABAYA MENGGUNAKAN METODE HIRARC - Chantya Wulan Pamungkas; Lidya Ayu Novita; Luthfiyah Nurul Khoirunnisa; Marizha Putri Amalia; Denny Oktavina Radianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Work accidents are the main focus in the world of occupational safety and health. Work accidents can occur in a company or agency, including the Surabaya State Shipbuilding Polytechnic (PPNS) in which there is a machining workshop. This journal was created to analyze the possibility of accidents that can occur so that they can be prevented. The method used to prevent and minimize accidents in the machining workshop at PPNS is HIRARC (Hazard Identification Risk Assessment and Risk Control). The results obtained from work activities in the machining workshop are 17 low risk categories, 11 medium risk categories, and 3 with high risk categories